The Correlation of Vitamin D Levels and Ghrelin, Adiponectin, and Resistin Levels Among Post-Ischemic Stroke Patients - Santoso Jaeri; Retnaningsih Retnaningsih; Amin Husni; Nani Maharani; Gemala Anjani (Medica Hospitalia : Journal of Clinical Medicine, 2025)
BACKGROUND: Dyslipidemia is one of the modifiable risk factors for stroke. The pathogenesis of dyslipidemia is through several mechanisms including adipose tissue-mediated adiponectin, resistin, and leptin secretion. Vitamin D is correlated with lipid profiles, but there is no evidence of the role of vitamin D in ghrelin, adiponectin, and resistin secretion, which may contribute to the mechanisms of the impairment of lipid profile among post-ischemic stroke. AIMS: To determine the correlation between vitamin D and ghrelin, adiponectin, and resistin among post-ischemic stroke. METHODS: An observational analytic study with a cross-sectional approach was conducted among forty post-ischemic stroke patients which was obtained consecutively. The serum vitamin D, ghrelin, adiponectin, and resistin levels were measured using the venous blood obtained from the median cubital vein. Data analysis was performed using the Spearman correlation test to determine the correlation between the serum vitamin D levels, ghrelin, adiponectin, and resistin levels. RESULT: The age of our subjects is approximate 57 years old with the proportion of males being more than female subjects. There is a significant association between serum vitamin D levels and gender, total energy as well carbohydrate diet but no significant association between hormonal status and the characteristics of subjects was revealed. Furthermore, there is no significant correlation between serum vitamin D levels with the hormonal status of ghrelin, adiponectin, or resistin levels (p=0.994; 0.395; 0.858, respectively). CONCLUSION: There is no significant correlation between serum vitamin D levels and serum ghrelin, adiponectin, or resistin levels among post-ischemic stroke patients